A Case-Control Study of the Associations between EGLN1 Gene Polymorphisms and COPD - Xin Li; Peng Zhang; Jing Yu; Chunyan Zhang; Yanli Shi; Xueyan Wei; Honge Li; Xuhui Zhang; Ao Lin; Zhen Yang; Yunchao Wang; Xinhua Wang (Frontiers in Bioscience-Landmark, 2024)
Background: Environmental and genetic factors are jointly involved in the development of chronic obstructive pulmonary disease (COPD). The EGLN1 gene is a major factor in upstream regulation of the hypoxia-inducible pathway. EGLN1 negatively regulates the hypoxia-inducible factors HIF-lα and HIF-2α by regulating the concentration of oxygen, mainly in a hypoxic environment. Hypoxia is a common physiologic condition during the progression of COPD, and several studies have identified genetic variants in EGLN1 as a key factor in the adaptation to hypoxic environments. However, it is still unclear whether there is an association between EGLN1 variants and the risk of developing COPD. Methods: A case-control study was conducted in the Gannan Tibetan Autonomous Prefecture, Gansu Province. A total of 292 COPD patients and 297 healthy controls were enrolled to assess the association of EGLN1 single nucleotide polymorphisms (SNPs) (rs41303095 A>G, rs480902 C>T, rs12097901 C>G, rs2153364 G>A) with COPD susceptibility. Results: The EGLN1 rs41303095 A>G, rs480902 C>T, rs12097901 C>G, and rs2153364 G>A polymorphisms were not associated with COPD susceptibility (p > 0.05). Conclusions: The EGLN1 rs41303095 A>G, rs480902 C>T, rs12097901 C>G and rs2153364 G>A polymorphisms were found in this study not to be associated with susceptibility to COPD in Gannan Tibetans.